Samoa Trade Facilitation Challenges for Women Traders and Freight Forwarders : Survey Findings and Recommendations - World Bank (World Bank, Washington, DC, 2021)
Trade is widely recognized to be an engine of growth that creates jobs, reduces poverty, and increases economic opportunity. Trade facilitation measures are non-discriminatory and apply to all traders in their design; however, these measures may not necessarily impact or benefit all traders in similar ways. There is a global lack of data on how trade facilitation interventions impact traders by gender at the firm level. There is also a global vacuum of knowledge of the exact proportion of cross-border traders that are women. Few countries, if any, can easily confirm the number of women that undertake cross-border trade in their respective countries. Designing interventions that are inclusive, benefiting women as well as men, is difficult without accurate data on the gander of those who participate actively in cross-border trade. Without this knowledge and that of the exact challenges faced by both genders, it is also hard to tell how much any subset of the economy would be impacted by any intervention. This lack of data may also reinforce the bias against women in trade policy making. This note presents findings of the survey work in Samoa. Samoa is a small archipelago, and the Apia seaport serves as the international gateway for almost 100 percent of all freight imports and exports for the country. Inter-island freight transport also depends on access to Apia Port.